1990
DOI: 10.1203/00006450-199006000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effects on Diastolic Ventricular Interaction during Development

Abstract: ABSTRACT. The effects of the pericardium on myocardial diastolic ventricular interaction during early development were determined in vitro using hearts excised from eight preterm (109 f 0.106 SE d gestation; term = 147 d) and eight newborn (2.3 + 0.30 SE d postnatal age) lambs. The lamb hearts were excised with the pericardium intact and immersed in a cold cardioplegic solution. Subsequently, very compliant balloon catheters were inserted into the right and left ventricles retrograde through the pulmonary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The newborn's hypertrophied right ventricle and pericardial constraint may increase ventricular interdependence in our animals as compared to the series performed in the adult [34]. In addition, it has been shown that improved cardiac performance with increased intrathoracic pressure was limited to subjects in acute ventricular failure in whom afterload is the dominant determinant of cardiac function [38,39].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The newborn's hypertrophied right ventricle and pericardial constraint may increase ventricular interdependence in our animals as compared to the series performed in the adult [34]. In addition, it has been shown that improved cardiac performance with increased intrathoracic pressure was limited to subjects in acute ventricular failure in whom afterload is the dominant determinant of cardiac function [38,39].…”
Section: Discussionmentioning
confidence: 79%
“…However, echocardiographic examination of the right ventricle is limited by the irregular shape, trabeculations of the walls, and the location of the right ventricle in the chest [14]. While measurements of the right ventricle would require a more invasive approach, the relatively high degree of ventricular interdependence at this age suggests that the right ventricle might respond in a similar fashion [34].…”
Section: Discussionmentioning
confidence: 99%
“…The incision across the base of the pericardium was left open, but the pericardial sac still enclosed the heart to maintain direct ventricular interactions (26). Two cuffed vascular occluders were placed around the main pulmonary artery and the descending aorta to control right and left ventricular afterloads, and an electromagnetic transducer (Statham, Oxnard, CA) was placed on the ascending aorta to measure flow.…”
mentioning
confidence: 99%